Indonesia's Climate Diplomacy under Joko Widodo: Shaping Equitable and Sustainable Global Future - Gaora, Putra Ansa; Pedrason, Rodon; Herman, Erry; Irene, Irene; Sylvia, Sylvia (Nation State: Journal of International Studies, 2023)
Climate change is a significant global concern due to its potential for long-term detrimental impacts on multiple facets of life. However, prevailing viewpoints on climate change often exhibit a bias towards the interests of the global north, disregarding the needs and vulnerabilities of the Global south. This research utilizes qualitative descriptive methods, integrating theories of international relations, climate diplomacy, and Indonesian foreign policy to offer a comprehensive explanation. Indonesia, being highly susceptible to climate change impacts, plays a pivotal role in addressing this disparity. However, previous studies have overlooked the examination of how Indonesia can optimize its climate diplomacy efforts under President Joko Widodo's leadership. Analyzing Indonesia's climate diplomacy endeavors yields valuable insights for the country's contributions to global climate change solutions and addressing its vulnerabilities. This shapes Indonesia's future perspective on international relations, balancing its interests with the imperative for global cooperation. Indonesia's involvement under the leadership of President Joko Widodo in global climate change efforts is pivotal for fostering an equitable and sustainable future.